Optimizing Kedungombo Reservoir Operations to Meet Irrigation Water Needs - Teguh Wibowo; Cahyono Ikhsan; Rintis Hadiani (JURNAL INOVASI PENDIDIKAN DAN SAINS, 2026)
The Kedungombo Reservoir plays an important role in providing irrigation water for several irrigation areas in Central Java. However, the existing reservoir's operational conditions still face obstacles in meeting water needs, especially during low inflow during the dry season. This condition causes a water deficit that impacts the decline in reservoir operational performance. Therefore, evaluation and optimization of reservoir operations are needed to improve the effectiveness of meeting irrigation water needs. This study aims to analyze the operational performance of the Kedungombo Reservoir under existing conditions and evaluate improvements in reservoir operational performance after optimization using Solver. The analysis of the mainstay discharge was carried out using the Weibull method based on inflow data from 2015–2025 with the mainstay discharge scenarios Q20, Q50, and Q80. Irrigation water needs were calculated based on the cropping pattern and the service area of ​​the Kedungombo Reservoir irrigation area. Reservoir operation simulations were carried out using HEC-ResSim, while reservoir operation optimization was carried out using Solver with the objective function of minimizing the deficit in irrigation water needs. The results of the study indicate that the existing operating conditions have a reliability level of 66.44% at Q20, 54.72% at Q50, and 44.98% at Q80. After optimization, the reliability level increased to 74.86% at Q20, 73.73% at Q50, and 74.00% at Q80. In addition, optimization was also able to reduce the vulnerability value and increase the operational resilience of the reservoir. The results of the study indicate that reservoir operation optimization can increase the effectiveness of Kedungombo Reservoir management in meeting irrigation water needs